POLA KONSUMSI PETANI TERHADAP BARANG KREDIT RUMAH TANGGA DI JORONG KOTO TUO KENAGARIAN KOTO TUO KECAMATAN HARAU KABUPATEN 50 KOTA - Ramadhani "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is to find out how the community consumptionpatterns towards goods credit and what are the factors that affect farmersconsumption patterns towards goods of household credit in Jorong Koto TuoKenagarian Koto Tuo Kecamatan Harau Kabupaten 50 Kota. This type ofresearch are used by quantitative descriptive approach with the method ofquestionnaire. The result of the research shows that consumption patterns as seenfrom the relationship of the level of consumption patterns against income that isclassified as being idr 500.000 to idr 1.000.000 per month. It is influenced byseveral factors, among which the most dominant to its ease in credit payments andthe acquisition of goods. From this data are expected to research the resultsobtained can be a reference for consumers to reconsider the use of the creditservices in accordance with the consumer income.key words : credit, income, consumption patters